The effect of neodymium and yttrium on benzofuran hydrodeoxygenation performance over a bulk Ni2P catalyst. (February 2019) - Song, Hua; Dai, Xueya; Jiang, Nan; Yan, Zijin; Zhu, Tianhan; Li, Feng
Neodymium (Nd)- or yttrium (Y)- modified bulk Ni2 P catalysts (Nd-Ni2 P or Y-Ni2 P) have been successfully prepared and their catalytic performance in benzofuran hydrodeoxygenation have been investigated. The as-prepared catalysts were characterised by X-ray diffraction, N2 adsorption–desorption, CO uptake and X-ray photoelectron spectroscopy. The addition of Nd or Y, especially Nd, can increase the surface area of the catalysts and promote the formation of smaller and more highly dispersed Ni2 P particles. The Nd-Ni2 P catalyst showed the highest benzofuran hydrodeoxygenation activity of 95.3% and the O-free products yield of 74.6%, which gives an increase of 25.3% and 35.4% when compared with that found for Ni2 P.